Application of Five-Finger Hypnosis in Patients Experiencing Anxiety Due to CKD on Hemodialysis at RSD Gunung Jati, Cirebon City - Rahmatunisa, Ninis; Purbasari, Dwiyanti (INDOGENIUS, 2025)
Background & Objective: Decreased renal function leads to accumulation of metabolic waste that cannot be excreted, causing toxicity in the body and requiring renal replacement therapy such as hemodialysis. Anxiety experienced by hemodialysis patients can be managed using five-finger hypnosis, which reduces tension, stress, and anxiety. Method: This study applied a descriptive method with a case study approach. Result: The application of five-finger hypnosis for three days reduced anxiety levels in patients undergoing hemodialysis. Conclusion:  Five-finger hypnosis is effective for managing anxiety in patients receiving hemodialysis.